STUDI KOORDINASI OCR DAN GFR SALURAN DISTRIBUSI PENYULANG SANDA UNTUK MENINGKATKAN KONTINUITAS PELAYANAN - Aras Widya Pratama, I Putu Gede; Dyana Arjana, I Gede; Indra Partha, Cok. Gede (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUM, 2021)
The Sanda feeder is supplied by Antosari Substation through transformer unit II and it has 3 reclosers, they are pempatan recloser,bangsing recloser and palisan recloser. Based on the 2017 disturbance fault recapitulation data from PT PLN (Persero) Bali, it has been phasephase and 1-phase ground short circuit in Sanda feeders almost every month. One of the problems that often occurs in Sanda Feeders is when a phase-phase and 1-phase ground fault occurs at the end of the feeder network and causes simultaneous trips to the recloser at the base of feeder network, causing the Sanda feeder relay to blackout. This shows the system need to analyze the evaluation of the coordination settings for the OCR and GFR protection system on the recloser and Sanda Feeder relays to minimize disturbances so as to improve service continuity. The analysis and simuation results represent that, the existing setting conditions of OCR and GFR has coincide coordination curves and the grading time is still below 0.3 seconds. The calculation and simulation of OCR and GFR that are carried out show that the protection system works selectively in the absence of coincide coordinating curves and a time grading value above 0.3 seconds according to the IEC 60255 standard.